The Effect of Ouhyul Herbal Acupuncture Point Injections on Shoulder Pain after Stroke. (13th June 2013) - Seo, Yu-Ri; Jung, Woo-Sang; Park, Seong-Uk; Moon, Sang-Kwan; Park, Jung-Mi; Park, Joo-Young
Abstract : An effective and safe remedy for shoulder pain is needed as shoulder pain is a common complication of stroke and restricts recovery of patients. This study was carried out to evaluate the effect of Ouhyul herbal acupuncture point injection (O-API) on shoulder pain in patients with stroke. Twenty-four participants with shoulder pain after stroke were recruited and randomized to the O-API and control groups. Treatment was conducted for 2 weeks three times per week. We evaluated the effects of treatment with a numerical rating scale (NRS), painless passive range of motion (PROM) of external shoulder rotation, and the Fugl-Meyer Motor Assessment (FMMA) at baseline, each week, and 1 week after the final treatment. All measures were similar between the O-API and control groups at baseline. The O-API group showed significant improvement on the NRS compared with that in the control group after 2 weeks of treatment, and the treatment effect was maintained until the follow-up period. PROM decreased significantly in both groups, but the reduction was maintained only in the O-API group. No significant difference was observed on the FMMA between the two groups. O-API resulted in significant improvement in shoulder pain after stroke, and its effect was maintained after termination of treatment without any severe side effects.